al-Hira, Irak. Feldforschungen. Prospektionen und Ausgrabungen. Die Arbeiten im Jahr 2022 - Salman, Ibrahim; Gussone, Martin; Hof, Catharine; Müller-Wiener, Martina; Schneider, Agnes; Ullrich, Burkart; Ahmad, Mustafa (e-Forschungsberichte des DAI, 2023)
The late antique capital of the Lakhmid kingdom of al-Hira, located in Mesopotamia, today in southern Iraq, was continuously settled from the Late-Antique to the Early Islamic period. Whereas its history is known through literary sources, its material existence is only little studied. The goal of the current cooperation project is to gain more information about the city based on archaeological evidence. This report presents the preliminary results of the fieldwork during the year 2022. Magnetometer prospection and a study of the surface features at selected find sites have revealed different types of building complexes. Susceptibility measurements were undertaken being part of a subproject to generate a reproducible work-flow for the automated analysis of magnetometer-data. Excavations carried out at two selected areas revealed a further church and the gate of a large compound respectively. They provide also stratigraphic sequences and three building phases. Quantitative evaluation of pottery indicates differences between the two excavated areas. Studying and analysis of the results of the interdisciplinary research are still in process and aim to provide an interregional contextualization.